Akibat Hukum Jual Beli Organ Tubuh Manusia dalam Hukum Positif di Indonesia - I Wayan Merta Jaya; Anak Agung Sagung Laksmi Dewi; I Maoe Hinggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Indonesia is a country whose population is located on various islands in various regions, has various backgrounds and different body conditions that make everyone has different conditions. This can be seen from the use of advances in science and technology as a solution in solving health problems which include treatment or healing of disease, recovery, care and health services. The purpose of this study is to determine the legal arrangements regarding the sale and purchase of human organs in positive law in Indonesia and criminal sanctions for perpetrators who buy and sell human organs in Indonesia. This study uses an empirical method using a statutory approach in analyzing and reviewing the research. The results showed that. The results of the study explain that the application of the law regarding the provisions of the legislation governing the sale and purchase of human organs has not been maximally implemented by law enforcement officers. Transparency of organs is still a pro and con on the one hand, this work can save a person's life, but on the other hand, a person can be penalized for transparency, which is different from other countries that allow someone to carry out organ transactions to save someone's life